Faith and its dynamics. Structuring condition of Christian Life - Martínez-Gayol Fernández, Nurya (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2017)
This article studies the transmission of faith, which is understood as a dynamism. We will attempt to demonstrate how faith, dynamic by its very nature, constantly generates new dynamisms in which it is expressed and made concrete, and by which Christian life is daily made a reality. It is this dynamic nature intrinsic to faith that gives rise to the possibility and the necessity of its transmission. To this end, we will first try to clarify in what sense it is possible to speak of faith as a dynamism, given that it is normally linked to ideas such as firmness, rootedness, and stability. Next, we will spend time demonstrating the intrinsically dynamic nature of faith. Lastly, we will explore, as examples, some of the dynamisms that arise from faith, dynamisms that, from an innate demand, tend to transmit faith. We will specifically highlight three dynamics: thinking faith, loving faith, and hoping faith.
Keywords: paradox; dynamic stability; thinking faith; loving faith; hoping faith.